2020
DOI: 10.1007/s11764-020-00861-3
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the effectiveness of self-initiated interventions to decrease pain and sensory disturbances associated with peripheral neuropathy

Abstract: Purpose A small number of studies report that patients with peripheral neuropathy (PN) who engage in activities that promote a sense of personal well-being and provide physical, emotional, or spiritual comfort have a better quality of life and higher levels of adjustment to the changes generated by their illness and accompanying symptoms. This systematic review sought to evaluate the effectiveness of self-management activities that patients with PN initiate themselves to relieve PN symptoms and improve quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 85 publications
(379 reference statements)
0
8
0
1
Order By: Relevance
“…To date, no review of CIPN-specific behavioural interventions has been conducted. A systematic review, focused on studies involving patient self-management to reduce symptoms of peripheral neuropathy (PN) caused by a range of conditions such as diabetes, HIV and other autoimmune disorders, reported that self-initiated interventions may reduce self-reported PN symptoms [26]. But results may not be wholly applicable when managing neuropathy in the context of cancer chemotherapy because CIPN is an unintended consequence of chemotherapy treatment that also brings associated psychosocial complexities [4].…”
Section: Introductionmentioning
confidence: 99%
“…To date, no review of CIPN-specific behavioural interventions has been conducted. A systematic review, focused on studies involving patient self-management to reduce symptoms of peripheral neuropathy (PN) caused by a range of conditions such as diabetes, HIV and other autoimmune disorders, reported that self-initiated interventions may reduce self-reported PN symptoms [26]. But results may not be wholly applicable when managing neuropathy in the context of cancer chemotherapy because CIPN is an unintended consequence of chemotherapy treatment that also brings associated psychosocial complexities [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, a previous review on self-initiated interventions among patients with cancer with peripheral neuropathy showed that strategies were beneficial in reducing symptoms and concerns. 107 …”
Section: Discussionmentioning
confidence: 99%
“…Advanced cancer was defined as any hematological cancer or any solid tumor with locally or systemically advanced disease (The Union for International Cancer Control Tumor, Nodes, and Metastases Classification of Malignant Tumors (UICC TNM) Stage of III-IV or equivalent) [26]. Self-management strategies were defined as interventions that were administered by the person with cancer or their caregivers, including those initiated with support from a health professional as well as initiated independently [20,21]. Eligibility criteria is presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Additional suggested areas of research include those which have shown benefit in the general cancer population but are yet to be tested in advanced cancer. This includes low-cost and easily accessible interventions of massage, heat therapy, and meditation [20,59]. Future studies should also explore how non-pharmacological self-management interventions may best be implemented in conventional cancer care.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation